The gut microbiome and cross-reactivity of food allergens: current understanding, insights, and future directions - Carolina Taico Oliva; Ibrahim Musa; Daniel Kopulos; Fariba Ardalani; Anish Maskey; Aaron Wilson; Nan Yang; Xiu-Min Li; Xiu-Min Li; Xiu-Min Li (Frontiers in Allergy)
This mini-review examines the emerging role of the gut microbiome in influencing food allergen cross-reactivity. It specifically focuses on how microbial diversity, antigens, and metabolites impact IgE-mediated allergic responses. Cross-reactivity occurs when structurally similar food and microbial antigens trigger hypersensitivities, affecting millions of people worldwide. Recent research underscores the significance of microbial diversity in early life for developing immune tolerance. Beneficial strains, such as Lactobacillus and Bifidobacterium, play a crucial role in supporting the functions of T regulatory cells (Tregs) and immunoglobulin A (IgA). Additionally, we discuss microbial metabolites, particularly short-chain fatty acids (SCFAs), which enhance immune tolerance by promoting Treg differentiation and maintaining gut barrier integrity, thereby reducing allergen entry. However, it is important to note that SCFAs can provoke inflammatory responses under certain conditions, highlighting the necessity for targeted research on their dual effects. Dysbiosis-related intestinal permeability, often referred to as “leaky gut,” can further worsen cross-reactivity. Microbial antigens like lipopolysaccharides (LPS) are known to influence Th2-dominant responses.